The pathogenesis of chronic pancreatitis. - Sidhu, S. S. (BMJ Group, 1995)
To date, there is no consensus on the evolution of chronic pancreatitis. Comfort's initial proposal of acute pancreatitis progressing to chronic pancreatitis was discarded by protagonists of the 'separate' theory. Sarles thus stresses the de novo evolution of chronic pancreatitis-acinar protein hypersecretion associated with an imbalance of pancreatic stone promoting and inhibiting factors. However, the 'necrosis-fibrosis sequence' hypothesis of Kloppel and Mallet resurrects the probability of acute pancreatitis leading to chronic pancreatitis. Dimagno offers a unifying concept that the degree of acinar injury determines the natural history of pancreatitis. Uninhibited release of toxic free radicals could be a common end point for various aetiologies resulting in acute or chronic pancreatitis. The pathogenesis of chronic calcifying pancreatitis of the tropics is possibly no different from alcoholic chronic pancreatitis. Neurocrine and paracrine mechanisms have been offered to explain pain out of proportion to radiological and histological pancreatic abnormalities in minimal change chronic pancreatitis.